Wrinkling process in a single silicene sheet caused by in-plane shear. (1st November 2019) - Miao, Jianxiong; Zhou, Yang; Zhang, Qianhui; Jiang, Jinyang; Duan, Wenhui
Highlights: Wrinkles can initialize and grow rapidly as an increasing shear displacement is applied to a single silicene sheet. The wavelength and amplitude of the wrinkles are largely dependent on the shear strain. The MD simulation results agree with a continuum model. Abstract: The wrinkling process of a monolayer silicene sheet subjected to an increasing in-plane shear strain is investigated by molecular dynamics (MD) simulation. The results show that due to the weak in-plane stiffness of silicene, wrinkles can initialize and grow rapidly as shear displacements increase. Finally, an ordered arrangement of wrinkles can be formed, with crests parallel to each other and approximately the same size. The wavelength and amplitude of the wrinkles are largely dependent on the shear strain until the strain reaches a critical value that makes the size of wrinkles controllable. A continuum model is also employed to estimate the size of wrinkles, which is consistent with the MD simulation results. The findings in this work could advance understanding of the shear resistance of silicene sheets and promote their potential applications in strain sensors, flexible electronics and energy storage devices.